Characterization of Group I Metabotropic Glutamate Receptors in Rat and Human Adrenal Glands - Fan, Ya-nan; Li, Chaohong; Huang, Lu; Chen, Lingyun; Tang, Zhao; Han, Guangye; Liu, Yuzhen (Frontiers in Physiology, 2020)
Glutamate and its receptors have been demonstrated to promote both basal and nicotine-evoked catecholamine release in bovine chromaffin cells. Multiple glutamate receptors, including metabotropic glutamate receptors (mGluRs), are found in the adrenal glands of several types of species, as well as in cultured chromaffin cells. However, there is limited information available regarding the expression of GRM1-8 mRNAs and the detailed localization of group I mGluRs (mGluR1 and mGluR5) in the rat and human adrenal cortex and medulla. Therefore, we examined the mRNA expression of GRM1-8 subunits using RT-PCR and the distribution of mGluR1 and mGluR5 in the adrenal glands by applying immunostaining. Our results showed that the GRM1-8 mRNAs, except the non-detectable GRM1 in the rat adrenal cortex, were expressed in both the cortex and medulla of the rat and human adrenal glands. The immunostaining of mGluR1 revealed its localization only in adrenal medulla of rats and presence in both adrenal cortex and medulla in humans. In the adrenal medulla, the central part in adrenal glands, mGluR1 was detected in chromaffin cells, but not in nerve fibers and ganglion cells. The immunoactivity of mGluR5 was visible in the capillary wall throughout the adrenal cortex and medulla in rat and human samples. Its immunoactivity was also observed in the ganglion cells in the rat adrenal medulla. No mGluR5 immunoactivity was detected in the chromaffin cells and nerve fibers in rat and human adrenal medulla. Using dissected rat adrenal medulla as a model, we found that the treatment with mGluR1 agonist activated ERK1/2 and increased the expression of tyrosine hydroxylase (TH), a rate-limiting enzyme of catecholamine synthesis. Moreover, our result showed that mGluR1 signaling was involved in hypoxia-induced upregulation of TH in the dissected rat adrenal medulla. This study demonstrates the expression of GRM1-8 mRNAs in rat and human adrenal glands. Our data indicate that glutamate, through the activation of mGluRs, may play various physiological roles in the adrenal gland. Furthermore, mGluR1 may be involved in the biosynthesis of catecholamine by regulating TH, and mGluR5 may affect cortical and medulla hormone levels by regulating microvascular function.